Beyond auditor and auditee: exploring the governance of performance in eldercare. Issue 1 (2nd January 2023) - Ek Österberg, Emma; de Fine Licht, Jenny
ABSTRACT: Auditing is a key tool for governing performance. Informed by the 'audit trail logic' this article takes a micro-perspective on auditing in which the auditees play an active role. Using the case of eldercare, it explores what actors do as they take part in audits and how they make sense of the underlying logic. Findings reveal that the roles of auditor and auditee may not only shift between audits, but also blur during audit activities. Therefore, this article contributes to public performance literature and practice by empirically showing how actors involved in an audit negotiate a shared understanding of performance.